A rare manifestation of Escherichia coli septicemia - K, Abhilash; SV, Gigin (International Journal of Research in Medical Sciences, 2017)
Escherichia coli (E. coli) is an uncommon pathogen of adult bacterial meningitis. In adult patients it carries a high mortality. We are reporting a case of 65 year old diabetic male presented with fever, abdominal pain & altered sensorium. On evaluation he was found to have E. coli meningitis secondary to septicaemia following UTI by same organism. He was started on Meropenem, but later changed to Imipenem according to culture & sensitivity results. Patient responded well to treatment and got discharged after 2 weeks of hospital stay.